Obesity-Related Hypertension in Children - Brady, Tammy M. (Frontiers in Pediatrics, 2017)
Obesity and hypertension have both been on the rise in children. Each is associated with increased cardiovascular disease risk and both track into adulthood, increasing the prevalence of heart disease and related morbidity and mortality. All children should be screened for hypertension, but children with co—morbid obesity may not only particularly benefit from the screening but may also prove the most challenging to screen. Increased arm circumference and conical arm shape are particularly problematic when attempting to obtain an accurate blood pressure measurement. This review focuses on the unique aspects of hypertension evaluation and management in the child with co-morbid obesity. Specific traditional and non-traditional risk factors that may contribute to elevated blood pressure in children with obesity are highlighted. Current proposed pathophysiologic mechanisms by which obesity may contribute to elevated BP and hypertension is reviewed, with focus on the role of the sympathetic nervous system and the renin-angiotensin-aldosterone system. This review also presents a targeted treatment approach to children with obesity-related hypertension, providing evidence for the recommended therapeutic lifestyle change that should form the basis of any antihypertensive treatment plan in this population of at-risk children. Advantages of specific pharmacologic agents in the treatment of obesity-related hypertension is also reviewed.